The Signaling Pathways Associated With Breast Cancer Bone Metastasis - Song, Xuelian; Wei, Changran; Li, Xiangqi (Frontiers in Oncology, 2022)
Background Breast cancer (BC) is now the leading cause of cancer in women, and bone is the primary site of distant BC metastasis. BC bone metastasis seriously affects the quality of life of patients and increases the mortality rate. However, the mechanism of BC bone metastasis is not fully understood. Main Body Paget’s “seed and soil” hypothesis led experts to explore the relationship between surface markers and receptors in breast tumors and various growth factors in bone. The relevant breast tumor markers serve as “seeds”, and the bone microenvironment that is suitable for the survival of the tumor serves as the “soil”. These factors interact to make up an entire system and form feedback pathways that accelerate the production of various cytokines, attracting BC cells to migrate to bone tissue, which worsens the development of BC and seriously affects the prognosis of patients. This process is a vicious cycle. At present, there are seven major signaling pathways involved in BC bone metastasis: the OPG/RANK/RANKL signaling pathway, TGF-β signaling pathway, IGF system, PI3K-AKT-mTOR signaling pathway, Wnt signaling pathway and Hippo signaling pathway. In addition, FGF-FGFR signaling pathway, androgen-AR/LSD1-target gene pathway, Notch signaling pathway, JAK-STAT signaling pathway and CaN/NFATC1 signaling pathway also seem to be associated with BC bone metastasis. Conclusion This review focuses on the signaling pathways related to BC bone metastasis and explores the interactions among these pathways, which will lay a solid theoretical foundation for further understanding the mechanism of BC bone metastasis and developing effective targeted therapeutic drugs.